Four new species of Acoela from Chile - Kånneby, Tobias; Jondelius, Ulf (Zootaxa, 2013)
Acoels are with few exceptions marine worms and a common component of the interstitial meiofauna. In this study we present new species to science belonging to Isodiametridae and Solenofilomorphidae. The new species, Isodiametra finkei n. sp., Postaphanostoma nilssoni n. sp., Pseudaphanostoma hyalinorhabdoida n. sp. and Solenofilomorpha pellucida n. sp. were all collected in Chile during March 2012. Nucleotide sequences for the ribosomal genes 18S rDNA and 28S rDNA as well as COI mtDNA have been determined for the new species and used in a maximum likelihood analysis to further support their classification.